(3OQQ GdfMhQ aj eOM Gdedc GdefUhQs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s ((3fhQ GdOjf Hf Ydi Hf MSjf Hf CHj GdMSf s)
(3ChdgG (B:s
(3CfJ GdhUGd eNGaI GdQbHGA hGJJc JMJ eOGQY GdXdeGA GUaJc ef HYO GdUOhQ ehOI hcPG GdOhGi jchf HYO GdOGi s
(3BNQgG (B:s
(3jefgG Gdfhe ai PQGc adG RdJ jef fGe hYjTi QVi jGfY GdYhO UGMH GdLhO MJa GdYOh haJM Gdhdi JeJ OQQ GdfMhQ ai eOM Gdedc GdefUhQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B141s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B750s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs